PROTECTING THE CHILD VICTIM IN SEXUAL OFFENCES: IS THERE A NEED FOR SEPARATE LEGAL REPRESENTATION? - Desan Iyer; Lonias Ndlovu (Obiter, 2021)
The number of children being sexually violated on a daily basis continues to escalate against a backdrop of a dearth in the conviction rate of their attackers. This is notwithstanding global efforts being made to protect children from the harrowing experience of being sexually violated. Creative measures such as the introduction of innovative child legislation have been largely neutralized by the inability of the criminal justice system to complement the child’s healing process. The gulf between policy and practice has given rise to a lack of protection in respect of the rights of children. In this paper, we seek to highlight the gaps in the South African criminal justice system when it comes to safeguarding the interests of the minor complainant during the criminal process. We analyse key legislative instruments which purport to protect the minor victim. The analysis is aimed at determining whether or not the specified key provisions are in conflict with the Constitution. The introduction of separate legal representatives for child complainants is evaluated as an option in improving the plight of young child victims. The paper then concludes on an optimistic note by boldly opining that in line with legal developments in other international jurisdictions, the South African criminal justice system can accommodate the legal novelty of introducing separate legal representation for child victims.